A hybrid fuzzy-repetitive control scheme for single-phase CVCF inverters - Li Jian; Kang Yong; Chen Jian (2002 28th Annual Conference of the IEEE Industrial Electronics Society, 2002)
In this paper a hybrid fuzzy-repetitive control scheme for single-phase CVCF inverters is presented. The performance of CVCF inverters is evaluated in terms of output voltage waveform distortion with linear or nonlinear loads and transient response due to sudden changes in the load. The fuzzy PD controller is used to improve transient performance whenever the system exhibits an oscillatory or overshoot behavior. It preserves the simple linear structure of the conventional PD controller yet enhances its self-tuning control capability. However, fuzzy PD controller cannot provide good small-signal response. So repetitive control is applied to generate high-quality sinusoidal output voltage in steady state. Repetitive control can be regarded as a simple learning control because the control input is calculated using the information of the error signal in the preceding periods. The repetitive controller is synthesizing to minimize low-order harmonic distortion. Thus, the fuzzy PD controller and repetitive controller can be combined to take advantage of their positive attributes. The control scheme is implemented using a TI TMS320F240 DSP in a 400 Hz 6 kW prototype. Simulation and experimental results prove that the proposed control scheme can achieve not only low THD during steady-state operation but also fast transient response subject to load step change.